2010
DOI: 10.1177/147323001003800622
|View full text |Cite
|
Sign up to set email alerts
|

Modified Natural Cycle for In Vitro Fertilization and Embryo Transfer in Normal Ovarion Responders

Abstract: Controlled ovarian hyperstimulation (COH) using a gonadotrophin-releasing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Eight studies evaluated milder ovarian stimulation compared to the long‐agonist protocol. Five studies used mild protocols with a GnRH antagonist and hCG triggering, one used clomiphene citrate and hMG, one used hMG only and one used less FSH in an agonist protocol. They all reported OHSS and clinical pregnancy rates; the average rate of OHSS in the control groups was 4.6%.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies evaluated milder ovarian stimulation compared to the long‐agonist protocol. Five studies used mild protocols with a GnRH antagonist and hCG triggering, one used clomiphene citrate and hMG, one used hMG only and one used less FSH in an agonist protocol. They all reported OHSS and clinical pregnancy rates; the average rate of OHSS in the control groups was 4.6%.…”
Section: Resultsmentioning
confidence: 99%
“…Although European studies have concluded that mild-IVF was cost-effective over conv-IVF when medications were minimized, no such comparison of mild-IVF and conv-IVF has been undertaken in the United States (US) [16] [19] [20]. As both costs and expected pregnancy rates in the United States are, on average, higher than reported European rates, application of a European assessment on cost-effectiveness is difficult in the US [21]- [23].…”
Section: Introductionmentioning
confidence: 99%
“…A few retrospective non-RCTs showed no cost savings comparing CCþGn cycles with GnRH agonist down-regulation cycles (53,54). However, many RCTs, including the one previously mentioned here, found MS-IVF to be significantly less expensive (22,23,29).…”
Section: Lower Financial Costmentioning
confidence: 72%
“…The systematic review by Matsaseng et al (15) reported a significantly higher CCR with MS-IVF among normal responders (16% vs. 9%; OR 2.55, 95% CI 1.62-4.02). However, many other RCTs, not included in this meta-analysis, found no difference in CCRs when MS-IVF was compared with C-IVF in normal responders (7,23,26,28,29). Interestingly, the Cochrane review that included CCþGn as a ''mild stimulation'' regimen found higher CCR mainly in those RCTs in which a GnRH antagonist was not used to suppress endogenous LH, implying a decline in CCRs with antagonist cotreatment (36).…”
Section: Potential Limitations Of Ms-ivfmentioning
confidence: 81%